2012
DOI: 10.1177/039463201202500218
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nebulized Hypertonic Saline and Epinephrine in Hospitalized Infants with Bronchiolitis

Abstract: The objective of the study is to verify effects of nebulized 3% saline hypertonic solution (HS) in comparison to normal saline (NS) in addition to epinephrine in hospitalized children with bronchiolitis. Infants were randomly assigned either to receive every 6 hours nebulized NS (group I) or 3% HS (group II) in addition to epinephrine (1.5 mg) and to conventional treatment. The main endpoints of this study were the length of stay (LOS) in hospital and the clinical response score (CSS). Patients presented a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 18 publications
4
73
2
Order By: Relevance
“…9,[11][12][13][14] Our results challenge the conclusions of the most recent Cochrane review of HS, 18 which suggests a potential benefit of HS. We believe this is partly attributed to the 2 to 3 times longer average LOS in the latter studies 9,[11][12][13][14] than in the studies in the United States and India. It is possible that HS has a greater effect when administered over a longer period of time than in an acute setting with a shorter LOS.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…9,[11][12][13][14] Our results challenge the conclusions of the most recent Cochrane review of HS, 18 which suggests a potential benefit of HS. We believe this is partly attributed to the 2 to 3 times longer average LOS in the latter studies 9,[11][12][13][14] than in the studies in the United States and India. It is possible that HS has a greater effect when administered over a longer period of time than in an acute setting with a shorter LOS.…”
Section: Discussioncontrasting
confidence: 84%
“…[15][16][17] Initial studies using HS for infants hospitalized with bronchiolitis suggest decreased LOS and improved severity scores. [9][10][11][12][13][14] Those studies differed from this study by excluding infants with previous wheeze, administering study medications with bronchodilators, or study subjects having much longer mean LOS. 9,10,13,14 A 2013 Cochrane review of HS in bronchiolitis referencing the aforementioned studies suggested 3% HS given with bronchodilators may be considered a safe and effective treatment of infants with mild to moderate bronchiolitis.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertonic saline was shown to be more effective than NS in improving bronchiolitis clinical scores in 5 studies 21,25,32,33,36 in both outpatient and inpatient settings, consistent with the results of Zhang et al 49 In the ED setting, both saline preparations, hypertonic or normal, were effective in reducing bronchiolitis scores. 26,28,30,31 The determination by the AAP that hypertonic saline is not effective in this setting is intriguing in light of the effectiveness of both forms of saline (NS and hypertonic saline) in these trials.…”
Section: Discussion/conclusionsupporting
confidence: 77%
“…Miraglia Del Giudice et al 36 conducted a prospective, double-blind, randomized, controlled trial to assess the effects of nebulized epinephrine plus either 3% hypertonic saline or NS in hospitalized children with bronchiolitis in Italy. They assessed 2 main outcomes: 1) the difference in LOS between the 2 groups and 2) the change in CSS from baseline between the 2 groups.…”
Section: Clinical Trials Evaluating Hypertonic Saline Use In Hospitalsmentioning
confidence: 99%